2016
DOI: 10.2147/ndt.s100634
|View full text |Cite
|
Sign up to set email alerts
|

A meta-synthesis on parenting a child with autism

Abstract: BackgroundThe lifelong nature of autism in a child has deep implications on parents as they are faced with a range of challenges and emotional consequences in raising the child. The aim of this meta-synthesis was to explore the perspectives of parents in raising a child with autism in the childhood period to gain an insight of the adaptations and beliefs of parents toward autism, their family and social experiences, as well as their perceptions toward health and educational services.MethodsA systematic search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
74
0
18

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(102 citation statements)
references
References 94 publications
(419 reference statements)
10
74
0
18
Order By: Relevance
“…To identify relevant studies, a targeted search strategy was implemented, involving (1) database searches (PsychINFO and Web of Science), (2) a review of studies citing or cited by those identified for inclusion on the basis of the database search, and (3) a review of articles included in two relevant existing meta-syntheses (one on parenting children with autism, the other on parents’ experiences of caring for children with ASD; Ooi et al 2016 ; DePape and Lindsay 2015 ). This approach was chosen because indexing of parenting strategies in response to problem behaviour in ASD within databases was poor.…”
Section: Methodsmentioning
confidence: 99%
“…To identify relevant studies, a targeted search strategy was implemented, involving (1) database searches (PsychINFO and Web of Science), (2) a review of studies citing or cited by those identified for inclusion on the basis of the database search, and (3) a review of articles included in two relevant existing meta-syntheses (one on parenting children with autism, the other on parents’ experiences of caring for children with ASD; Ooi et al 2016 ; DePape and Lindsay 2015 ). This approach was chosen because indexing of parenting strategies in response to problem behaviour in ASD within databases was poor.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, improving the parents’ mental health and wellbeing enhances the potential of the child to also achieve a better quality of life. Improvements to the child’s overall behavior and functioning is facilitated when behavioral treatment interventions being delivered to the child are supplemented by continued implementation by the parent carers in the home environment [ 39 ]. The effectiveness of the child’s behavioral treatment interventions have been reported to be diminished when parents’ mental health needs are unmet [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, en las últimas décadas y debido al aumento de interés sobre este trastorno, la salud mental de los padres de estos pacientes se ha vuelto otro foco de atención. En este sentido, y a partir de la información encontrada en la literatura, los grandes ejes de estudio internacional sobre salud mental en estos padres se han focalizado principalmente en medir estrés, ansiedad y depresión (Dababnah & Parish, 2015;Golfenshtein, Srulovici y Medoff-Cooper, 2015;Gomes et al, 2015;Lee, 2013;Ooi, Ong, Jacob & Khan, 2016;Whitmore, 2016;Bonis & Sawin, 2016) por lo que, en esta revisión, esos serán los conceptos a considerar. No obstante, además de lo anterior, cabe destacar que la OMS (s.f.)…”
Section: Santé Mentale Et Interventions Pour Les Parents D'enfants Avunclassified
“…Lo anterior va en concordancia con lo señalado por Conner, Maddox y White (2013), quienes refieren que esta temática se ha estado explorando recientemente y quizá, debido a esto, se comprenda la escasa cantidad de estudios en padres de niños con TEA. No obstante, los pocos estudios que han evaluado ansiedad han sido en muestras de padres de preadolescentes y adolescentes con TEA (Ooi et al, 2016;Conner et al, 2013;Uljarevic et al, 2016). En este sentido, resultaría interesante el estudio de esta variable en padres de individuos con TEA a lo largo del ciclo vital de sus hijos, pudiendo observar si existen variaciones dependiendo de la etapa del desarrollo.…”
Section: Ansiedadunclassified